GENETIC EVALUATION OF MILK PRODUCTION TRAITS IN LOCAL GOAT - Yousif M. S. Al-Barzinji,; Fahad K. Zainal, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted on 67 local doe goat, aged from 2-5 years old. The overall mean of TMY, DMY and lactation length of 1st and 2nd flocks were (130.541 ± 7.403 kg, 0.716 ± 0.033kg, and 182.432 ± 4.112 day) and (164.043 ± 8.788 kg, 0.832 ± 0.043 kg, 197.027 ± 2.650 day), respectively. The flock, age of doe, doe coat color, month of kidding and type of birth have significant effect on TMY and DMY, doe in 2nd flock production 33.502 and 0.116 kg milk/doe, respectively more than doe in 1st flock. Doe of five years old yielded (181.878 ± 10.171 kg /doe) and (0.892 ± 0.044 kg /doe/day) more milk than young doe. Doe kidding in Januarys were consistently produced high significantly (p≤0.001) more TMY (158.354 ± 7.076 kg /doe) and DMY (0.828 ± 0.033 kg /doe/day) in comparison with other groups. Doe with brown coat color produced significantly (p≤0.05) more TMY (165.205 ± 20.558 kg /doe) and DMY (0.835 ± 0.095 kg /doe/day) in comparison with other coat colors. Doe kidding twin’s kids were significantly (p≤0.05) yielded more TMY and DMY than single kids. The flock and age of doe significantly affected the lactation length, 2nd flock have higher length with 197.027 ± 2.650 day and higher lactation length recorded of doe with 5 years old with 200 ± 3.779 day.  BLUP values for TMY of doe ranged from -130.65 to 224.77 kg/doe.  The repeatability of DMY, fat%, protein% and lactose% in present study arrived 0.286, 0.319, 0.067 and 0.015 respectively. The MPPA value of TMY in this study ranged from 80.988 to 329.749. These results indicated the good genetic make-up of local goat for milk traits and the selection programs can play major role to increase production ability of local goat.